EKSPLORASI ETNOMATEMATIKA MOTIF BATIK GONGGONG TANJUNGPINANG KEPULAUAN RIAU - Sahilda, Yuntira; Izzati, Nur (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Batik is a culture of the archipelago in Indonesia, where batik has its own characteristics, one of which is barking batik in Tanjungpinang City, Kepulauan Riau Province. In the batik motif there is an indication of mathematical practice, especially in the batik motif. Mathematical practice in this culture is known as ethnomatematics. This study aims to explore ethnomatemics on the batik motifs of Tanjungpinang, Kepulauan Riau Province . This type of research is qualitative with an ethnographic approach. Research data is done through observation, interviews and documentation. The main instrument of research is the researcher himself. Then the data are analyzed by referring to Van Maanen by reducing data, data presentation and conclusions. The results showed a mathematical practice of the bark batik motifs in the form of the concept of folding symmetry, acute angles, obtuse angles, translational concepts, and circular planes.